Upaya Meningkatkan Kemampuan Membaca dengan Menggunakan Strategi Pembelajaran KWL (Know-Want to Know-Learned) Berbantuan Media Cerita Bergambar pada Klas III SDN-3 Palangka Raya: Efforts to Improve Reading Ability Using the Knowledge-Want to Know-Learned KWL (Know-Want to Know-Learned) Media-Based Picture Story in Class III of SD-3 Palangka Raya - Erna Ningsih; Misyanto Misyanto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to describe the increase in the reading of students taught by using the KWL (Know-Want-to-Know-Learned) learning strategy assisted with pictorial story media, as well as knowing the reading activities of students who are trained using the KWL learning strategy Learned) aided by a picture story media. This type of research is Class Action Research (CAR). The subjects in this study were class III SDN-3 Langkai Palangka Raya students totalling 20 students and students. This data collection technique is observation and testing. Data analysis techniques are based on the results of the cycle during the learning process. The results showed that the use of the Know-Want-to-Know-Learn (KWL) learning strategy assisted with pictorial story media could improve reading skills in Grade III SDN-3 Langkai Palangka Raya students. This is based on the results of the study with the acquisition of values in the learning activities that have been carried out for two cycles. It can be concluded that: The use of Know-Want to Know-Learned learning media assisted with pictorial stories can improve students' reading skills. , this can be seen from the pre-action average = 58 average with classical completeness 50% first cycle = 72 average with 75% artistic completeness and cycle II = 93 average with 100% traditional instruction.